Organic cultivation induced regulation in yield formation, grain quality attributes, and volatile organic compounds of fragrant rice. (30th March 2023) - Ruan, Shaoyi; Luo, Haowen; Wu, Feida; He, Longxin; Lai, Rifang; Tang, Xiangru
Highlights: Organic cultivation produced fragrant rice with lower grain yield. Organic cultivation produced fragrant rice with higher 2-acetyl-1-pyrroline content. Organic cultivation reduced intensities of seven sensory flavors of fragrant rice. Organic cultivation caused the absence of 56 volatile organic compounds. Organic cultivation caused the exclusive presence of 10 new volatiles. Abstract: Organic cultivation is an eco-friendly planting strategy. To explore the effects of organic cultivation on yield, grain quality, and volatile organic compounds of fragrant rice, the present study conducted a field experiment with organic cultivation and inorganic cultivation treatments over two subsequent growing seasons. The late season rice was sent for the determination of untargeted flavoromics using GC × GC-ToF-MS. Meanwhile, the GC × MS were used for the quantification of 2-acetyl-1-pyrroline. Our results showed that compared with inorganic cultivation, organic cultivation increased grain 2-AP and amylose contents by 21.19–26.10 % and 4.51–7.69 %, respectively. 5.89 %-15.55 % lower crude protein contents were recorded in organic cultivation. The results of untargeted flavoromics showed that organic cultivation caused the absence of 56 volatiles and the exclusive presence of 10 new volatiles compared with inorganic cultivation. In conclusion, organic cultivation produced fragrant rice with lower yield and higher 2-AP content as well as different flavor profiles.